2020
DOI: 10.3390/jcm9061702
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Involved in Cardiomyopathies and in Cancer

Abstract: Cancer therapy-induced cardiomyopathy (CCM) manifests as left ventricular (LV) dysfunction and heart failure (HF). It is associated withparticular pharmacological agents and it is typically dose dependent, but significant individual variability has been observed. History of prior cardiac disease, abuse of toxics, cardiac overload conditions, age, and genetic predisposing factors modulate the degree of the cardiac reserve and the response to the injury. Genetic/familial cardiomyopathies (CMY) are increasingly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 161 publications
0
6
0
3
Order By: Relevance
“…Hereditary/familial cardiomyopathy (CMY) is an autosomal dominant monogenic disease with no clear cardiac abnormality ( 12 ). Hypertrophic cardiomyopathy (HCM) has the highest incidence among CMY, followed by dilated cardiomyopathy (DCM), arrhythmogenic cardiomyopathy (ACM), and restrictive cardiomyopathy ( 13 ). In 2012, Truncations of titin ( TTN ) was first proposed as a DCM related gene, which encodes myotin in sarcomere ( 14 ).…”
Section: Relationship Between Cancer and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary/familial cardiomyopathy (CMY) is an autosomal dominant monogenic disease with no clear cardiac abnormality ( 12 ). Hypertrophic cardiomyopathy (HCM) has the highest incidence among CMY, followed by dilated cardiomyopathy (DCM), arrhythmogenic cardiomyopathy (ACM), and restrictive cardiomyopathy ( 13 ). In 2012, Truncations of titin ( TTN ) was first proposed as a DCM related gene, which encodes myotin in sarcomere ( 14 ).…”
Section: Relationship Between Cancer and Cardiovascular Diseasementioning
confidence: 99%
“…90% of patients with CCM received anthracyclines. An animal study showed that mice with TTNtv showed left ventricular cardiomyocyte elongation and dysfunction after treatment with anthracycline ( 13 ). In addition, desmosomes, as the main structure of the connections between cells, inhibit cell motor ability.…”
Section: Relationship Between Cancer and Cardiovascular Diseasementioning
confidence: 99%
“…Однако острая сердечная дисфункция также может отражать повреждение миоцитов, которое в конечном итоге может перерасти в раннюю или позднюю КТ. Не существует проверенных стратегий, позволяющих определить, является ли сердечная дисфункция обратимой или прогрессирующей, тем не менее повышение сердечных биомаркеров (мозгового натрийуретического пептида и сердечного тропонина) может быть способом выявления пациентов с долгосрочным риском КТ [16]. Ранняя хроническая КТ проявляется в виде систолической или диастолической ДЛЖ.…”
Section:  антрациклиновая кардиотоксичностьunclassified
“…В дополнение к TTNtv в ходе исследования были выявлены редкие белок-изменяющие варианты в пяти генах, ассоциированных с ДКМП: BAG3, LMNA, MYH7, TNNT2, TCAP [31]. Варианты MYH7 были идентифицированы в единичных случаях у пациентов с эпирубицин-индуцированной кардиомиопатией [16]. Также варианты мутаций саркомерного гена, кодирующего тяжелые цепи миозина (MYH7), были определены другими авторами у пациентов с тяжелой формой кардиомиопатии.…”
Section:  роль полиморфизмов генов в развитии антрациклин-индуцирова...unclassified
See 1 more Smart Citation